The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1001/jamaneurol.2019.1148
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statin Use and Risk of Dementia After a Concussion

Abstract: oncussions are a common cause of brain injury occurring in more than 1 million Americans each year and disproportionately involving older adults. 1-4 The subacute consequences vary widely and include fatigue, headache, irritability, insomnia, inattention, photophobia, vertigo, and cognitive difficulties. 5-9 Most patients recover from a concussion within weeks, although some can develop lingering mood disorders or chronic neuropsychiatric disorders. 10-14 The extent of complications after a concussion is uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 120 publications
2
31
0
Order By: Relevance
“…They suggest future RCTs as statins might mitigate injury-related brain oedema, oxidative stress, amyloid protein aggregation, and neuroinflammation. 72 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…They suggest future RCTs as statins might mitigate injury-related brain oedema, oxidative stress, amyloid protein aggregation, and neuroinflammation. 72 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…Some studies have also shown that statins reduce periodontal inflammatory injury (Subramanian et al, 2013). In a population-based cohort study, the use of statins was associated with a reduced risk of stroke after a concussion (Redelmeier et al, 2019). It can be postulated that statins have a protective effect against stroke and therefore reduce the risk of dementia (Redelmeier et al, 2019;Subramanian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They also do not cause hepatotoxicity, renal failure, cataracts11 or dementia 12. If anything, statins reduce the risk of dementia,12 13 as would be expected: cholesterol lowering prevents strokes, and preventing strokes is at present the best available way to prevent dementia 14 15. With the rare exception of autoimmune statin myopathy,16 probably the only valid causally related adverse effects are myopathy and a slight increase in the risk of diabetes,10 probably both due to impaired mitochondrial function resulting from depletion of ubiquinone 12…”
Section: Withholding Therapy In Patients Whose Subgroup Was Not Inclumentioning
confidence: 97%